INTEGRASI MEDIASI KASUS PERCERAIAN DALAM BERACARA DI PENGADILAN AGAMA - Saifullah, Muhammad (Faculty of Shariah and Law, State Islamic University (UIN) Walisongo, 2014)
This research aims to determine the implementation of mediation in divorce cases in The Religion Court Semarang, the substance perspective for PerMA No. 1 of 2008 on Mediation Procedure in the Court, and the legal culture for citizen proposing their problem to the court. This study uses the non-doctrinal law approach that puts the law as